1989
DOI: 10.1159/000234999
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Alterations Inducible by Mercury Compounds

Abstract: We determined the levels of total IgE, IgG and IgM in the sera of HgCl2 and gold sodium thiomalate (GST) treated A.SW, C57Bl/6, and DBA/2 mice. In HgCl2 treated A.SW mice, IgE and IgG levels increased up to 30 times above normal. In C57Bl/6 mice HgCl2 induced a slight IgE increase, but no change in IgG. Strain DBA/2, by contrast, did not show significant increases in either IgE or IgG. A.SW mice also proved susceptible to the immunostimulatory effects of GST in that they respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that in susceptible mouse strains, mercury treatment results in the formation of high levels of autoantibodies against nucleolar antigens [5][6][7]131. Many of these ANolA were found to be directed against fibrillarin, a 34-kDa protein, which is a component of the U3 and U8 small nuclear ribonucleoproteins [19][20][21].…”
Section: Mercury Induces Anola In Sjl Mice But Not In (Nzb X Nzw)fl mentioning
confidence: 99%
“…Several studies have demonstrated that in susceptible mouse strains, mercury treatment results in the formation of high levels of autoantibodies against nucleolar antigens [5][6][7]131. Many of these ANolA were found to be directed against fibrillarin, a 34-kDa protein, which is a component of the U3 and U8 small nuclear ribonucleoproteins [19][20][21].…”
Section: Mercury Induces Anola In Sjl Mice But Not In (Nzb X Nzw)fl mentioning
confidence: 99%